Revision of the millipede family Dalodesmidae in Madagascar, with descriptions of two new Malagasy species of Dalodesmus Cook, 1896 (Diplopoda, Polydesmida) - Thomas Wesener; Nesrine Akkari; Sergei I. Golovatch (ZooKeys)
The family Dalodesmidae Cook, 1896 in the fauna of Madagascar is reviewed and shown to presently encompass eight species in three genera: Dalodesmus Cook, 1896 (six species), Eutubercularium Brölemann, 1916 (one species), and Phymatodesmus de Saussure & Zehntner, 1897 (one species). These genera are diagnosed, and their respective species keyed, all being endemic to Madagascar proper and/or the immediately adjacent islets of Nosy Be and/or Nosy Sakatia. Dalodesmus currently contains six species, including two new, all supplied either with brief descriptive notes and available iconography or extensive descriptions and new illustrations, as follows: D. hamatus (Brandt, 1841), from an unspecified locality in Madagascar, now redescribed from a male specimen from Makira, northeastern Madagascar; D. odontopezus (Attems, 1898), from Nosy Be Isle; D. orator Hoffman, 1974, from Ambohimitombo, central Madagascar; D. tectus Cook, 1896 (= D. hova (de Saussure & Zehntner, 1897), syn. nov.), originally described from an unspecified locality in central Madagascar, with a male type and additional males identified as D. hova recorded from the Andasibe National Park (= Périnet) in east-central Madagascar. Additionally, two new species are described, D. speophilus sp. nov., from Grotte de Anjohibe, northwestern Madagascar, and D. kompantsevi sp. nov., from Montagne d’Ambre, northern Madagascar. Both the type species of Dalodesmus and its synonym Tubercularium Attems, 1898, D. tectus and D. odontopezus, respectively, are partly revised and illustrated based on holotypes, while D. hamatus is duly described and illustrated based on the first discovery of a male. Both Eutubercularium and Phymatodesmus are still monospecific, comprising only E. voeltzkowi (Mesibov, Wesener & Hollier, 2018), from Nosy Be Isle, and P. sakalava (de Saussure & Zehntner, 1901), from Andasibe, respectively. The latter species is fully redescribed and illustrated for the first time from male material.